High-performance human resource practices and firm performance: the mediating role of employees' competencies and the moderating role of climate for creativity. Issue 10 (31st May 2018) - van Esch, Emmy; Wei, Li Qun; Chiang, Flora F. T.
Abstract: Drawing on the resource- and competency-based view, this paper examines the relationship between high-performance human resource (HR) practices and firm performance. Using a sample of 189 firms in mainland China, a positive relationship between high-performance HR practices and firm performance was found that was partially mediated by employees' competencies. We also found the organisational climate for creativity to strengthen such relationship. The implications and future directions of these findings are discussed.